PERANAN FINANCING TO DEPOSITE RATIO DAN RETURN ON EQUITY DALAM MENINGKATKAN RETURN ON ASSET PADA BANK SYARIAH MANDIRI - Sundari, Asri; Benfidastafo, Beny (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2021)
ABSTRACT The purpose of this research was to determine and analyze the financing to deposit ratio, return on equity and return on assets, the role of financing to deposit ratio and return on equity simultaneously and partially in increasing return on assets. The research method used was descriptive and explanatory methods with a sample size of 44 financial reports by a quarter of Bank Islamic Mandiri during the years 2009-2019. The data analysis method used in this research was a multiple linear regression analysis models with data processing software SPSS 20. Based on the results of the research, it was found that the financing to deposit ratio of Bank Islamic Mandiri was ranked first with a very healthy classification, return on equity was ranked first with a very good classification, and return on assets was ranked second with a relatively good classification. Financing to deposit ratio and return on equity simultaneously and partially role a significant role in increasing return on assets with a determination coefficient of 79.20%. The results showed that the partial financing to deposit ratio has a negative and significant role in increasing return on assets, while return on equity has a positive and significant role in increasing return on assets, and partially return on equity has a dominant role in increasing return on assets. The implication of thisresearch was to be able to increase return on assets, Bank Islamic Mandiri must increase return on equity and supported by a decrease in the level of financing to deposit ratio. Keywords: Financing to Deposit Ratio, Return on Equity, Return on Asset